Metastatic retinoblastoma of the parotid and submandibular glands: a rare case report - Ping Wang (BMC Ophthalmology, 2017)
Abstract Background Retinoblastoma is the most common intraocular malignancy occurring in children. It can metastasize to the regional lymph nodes, central nervous system and distant organs usually the bones and bone marrow and very rarely to the soft tissue. Here, we report a case of unilateral retinoblastoma in a 4-year-old girl accompanied by a large metastasis of the parotid and submandibular glands that developed about 6 months previously and gradually increased in size 5 months after enucleation of the left eye. Case presentation A 4-year-old girl with a history of unilateral retinoblastoma presented with a large, painful and worsening mass (about 20 × 23 cm) of the left side of the neck. Following surgery, the orbital tumour was completely resected, and the large tumour invasion range in the left side of the neck was not resected completely. Histopathological examination revealed retinoblastoma of the orbit and the parotid and submandibular glands. After chemotherapy and additional local radiotherapy on the parotid and submandibular glands, the tumour was inactive and stable. Conclusions Delayed detection and inappropriate management contribute to poor outcomes. Fundus examinations, education regarding the early signs of RB, and optimization of the therapeutic strategy for RB may play important roles in ocular health.